Knowledge, experiences, and perceptions of medications for opioid use disorder among Black Kentuckians - Paris B. Wheeler; Brittany Miller-Roenigk; Jasmine Jester; Danelle Stevens-Watkins (Annals of Medicine, 2024)
AbstractBackground Opioid overdoses have continued to increase at higher rates among Black Americans compared to people from other racial groups. Despite demonstrated effectiveness of MOUD in reducing risk of opioid overdose, Black Americans face decreased access to and uptake of MOUD. The current study aimed to examine the knowledge, perceptions, and experiences with MOUD among a sample of Black adults who use prescription opioids nonmedically in order to inform tailored efforts to improve MOUD uptake.Methods Data were derived from a larger study assessing cultural and structural influences on drug use and drug treatment among people who use prescription opioids nonmedically. Semi-structured qualitative interviews were conducted with 34 Black men and women across four generational cohorts: born 1955–1969; 1970–1979; 1980–1994; and 1995–2001. Participant responses were analyzed using thematic analysis.Results Nearly half of participants (44.1%) reported no knowledge or experience with MOUD. Among participants who had any knowledge about MOUD, four major themes regarding their perceptions emerged: MOUD Helps with Recovery; Not Needed for Level of Drug Use; Side Effects and Withdrawal; Equivalence with Illicit Drug Use. The majority reported negative perceptions of MOUD (52.6%), and the youngest cohort (born 1995–2001) had a higher proportion of negative perceptions (80%) relative to other age cohorts (born 1980–1994: 50%; 1970–1979: 75%; 1955–1969: 16.6%).Discussion Findings indicate a significant knowledge gap and clear points of intervention for improving MOUD uptake. Interventions to improve communication of health information in ways that are culturally relevant and tailored by age group can be used in conjunction with efforts to improve MOUD access among Black individuals who use opioids nonmedically.